Emotion Reactivity and Regulation in Maltreated Children: A Meta‐Analysis. Issue 5 (7th July 2019) - Lavi, Iris; Katz, Lynn Fainsilber; Ozer, Emily J.; Gross, James J.
Abstract : The many adverse effects of child maltreatment make the scientific investigation of this phenomenon a matter of vital importance. Although the relationship between maltreatment and problematic emotion reactivity and regulation has been studied, the strength and specificity of these associations are not yet clear. We examine the magnitude of the maltreatment—child‐emotion reactivity/regulation link. Studies with substantiated maltreatment involving children aged up to 18 were included, along with a smaller number of longitudinal studies (58 papers reviewed, encompassing more than 11, 900 children). In comparison to nonmaltreated children, maltreated children experience more negative emotions, behave in a manner indicative of more negative emotion, and display emotion dysregulation. We outline several theoretical implications of our results.